2016
DOI: 10.1504/ejim.2016.074472
|View full text |Cite
|
Sign up to set email alerts
|

Firm ownership and internationalisation: is it context that really matters?

Abstract: This paper considers the potential role played by different kinds of shareholders in the firms' international level, distinguishing the firms quoted in the UK from those listed in the countries of Continental Europe (France, Germany, Italy, Poland and Spain). Our results confirm that different kinds of ownerships affect the overall level of a firm's internationalization. Family ownership has a negative impact on foreign sales in the UK but not in Continental Europe, while Bank ownership has a negative impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…This cluster is also known for its high export rates due to the presence of several important foreign multinationals. The high number of specialized firms located in this small area has led to the development of new businesses and the rapid diffusion of knowledge among local actors (Majocchi, Odorici, and Presutti ). This urban cluster has already been the focus of previous international studies (Presutti, Boari, and Majocchi ).…”
Section: Methodsmentioning
confidence: 99%
“…This cluster is also known for its high export rates due to the presence of several important foreign multinationals. The high number of specialized firms located in this small area has led to the development of new businesses and the rapid diffusion of knowledge among local actors (Majocchi, Odorici, and Presutti ). This urban cluster has already been the focus of previous international studies (Presutti, Boari, and Majocchi ).…”
Section: Methodsmentioning
confidence: 99%
“…According to Filatotchev and Wright (2017, p. 458), "Governance factors may themselves be outcomes of various firmlevel characteristics within a dynamic perspective"for instance, "better performing companies may attract better independent directors" (Filatotchev and Wright, 2017, p. 458). With static studies, it is difficult to detect causal links between firms' organizational characteristics and internationalization (Filatotchev et al, 2001) and explore how institutional contexts evolve (Majocchi et al, 2016). Thus, future studies should use longitudinal data.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…According to some authors, differences in corporate governance [1] like ownership type (Majocchi et al, 2016), business group membership (Holmes et al, 2018;Strange et al, 2009) and board composition (Ilhan Nas and Kalaycioglu, 2016) can influence firms' internationalization decisions and export behavior (Bauweraerts et al, 2019;Cristiano, 2018;Dixon et al, 2015). For instance, they affect firms' access to resources and attitudes toward risk (Fernández and Nieto, 2006) but also cause internal conflicts (Aguilera et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that social capital development is strongly influenced by the environmental context in which business partners are embedded (Majocchi, Odorici, & Presutti, 2016). To control for this factor, we conducted our empirical research within a delimited geographic area.…”
Section: Samplementioning
confidence: 99%